The rare mantis shrimp Areosquilla indica (Hansen, 1976) (Crustacea, Stomatopoda) from the Great Barrier Reef: first Australian records of the genus and species - Ahyong, Shane T.; Wassenberg, Theodore J. (Zootaxa, 2015)
The rare mantis shrimp genus Areosquilla is recorded from Australia for the first time based on nine specimens of A. indica (Hansen, 1926) collected from the Great Barrier Reef. Morphological variation beyond that observed in previous accounts is reported. The present record and other recent discoveries bring the Australian stomatopod fauna to 152 species and 68 genera.